Inheritance of the "rat-tail" syndrome - R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1996)
A form of congenital hypotrichosis, commonly known as rat-tail, is characterized by the colored hair anywhere on the body being short, curly, malformed, and sometimes sparse and an abnormal tail switch. The "rat-tail" syndrome is controlled by interaction between two loci. Cattle that express this syndrome must have at least one gene for black color and be heterozygous at the other locus involved.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Rat-tail syndrome; Genetics; Breeds